Ticks and Mites: Economic Importance - Oryakhail, Qudratullah (Journal of Natural Sciences – Kabul University, 2025)
Ticks and mites belong to the order Acarina and infest a variety of plants and animals. These small, oval creatures have compact bodies without clear differentiation between the prosoma and opisthosoma. Their mouthparts are well adapted for biting, sucking, and piercing. The chelicerae and pedipalps are small and chelate, and they are associated with the mouthparts. The number of legs varies among the larval, nymphal, and adult stages. Mites are significant agricultural pests. They are smaller than ticks and are predatory, parasitic, and scavengers, with some species being microscopic. Mites inhabit nearly every habitat suitable for animal life, and certain species are parasitic to insects, farm animals, birds, and humans.